A Rare Cause of Ascites: Desmoplastic Small Round Cell Tumour - Tas, Adnan; Arhan, Mehmet; Aksoy, Sercan; Koklu, Seyfettin (Fırat University, 2013)
Desmoplastic small round cell tumour (DSRCT) is a malignant pathologic entity with a mesothelial origin. It is a rare neoplasm of small round cells located in the abdomen, mainly affecting male adolescents and young adults. Herein, we report a 17-year-old man presented with ascite and growing very fast abdominal mass. Laparoscopy was performed showing thickening of omentum and peritoneum and normal internal organs. Histopathological examination of the peritoneal samples concluded to desmoplastic small round cell tumor. The patient was treated according to the cyclophosphamide, vincristine and adriamisin. He responded chemotherapy and reduced intraabdominal, pelvic ascites and intraabdominal masses.

Dezmoplastik küçük yuvarlak hücreli tümör mezotelyal orjinli malign patolojilidir. Abdomende oldukça nadirdir ve başlıca genç erkeklerde görülür. Oldukça malign seyirlidir. Burada çok hızlı büyüyen abdominal kitle ve asidi olan 17 yaşında erkek hasta sunduk. Laparaskopide periton ve omentunmda kalınlaşma saptandı ve iç organlar normaldi. Histopatolojide periton örneklerinde dezmoplastik küçük yuvarlak hücreler saptandı. Hasta siklofosfamid, vinkristin ve adriamisin ile tedavi edildi. Kemoterapiye cevap verdi ve hastanın intraabdominal ve pelvik asidi ile inraabdominal kitlesi azaldı.
Asidin Nadir Bir Nedeni: Dezmoplastik Küçük Yuvarlak Hücreli Tümör